TEACHERS’ PEDAGOGICAL RESISTANCE OF EMI THROUGH CLASSROOM TRANSLANGUAGING IN NEPALESE SCIENCE CLASSROOMS - Khem Raj Rauteda; Bhawana Luitel (IJIET (International Journal of Indonesian Education and Teaching), 2025)
English as a Medium of Instruction (EMI) is an approach used to teach content subjects in English, particularly in regions where English is not the primary language of most of the population. The increasing adoption of EMI in Nepalese public schools has sparked debate among educators, policymakers, and linguists. While local bodies promote EMI, teachers often utilize Nepali and English, allowing students to use their home languages. However, the science teachers’ use of multilingual practices and resistance to exclusive English instruction remain underexplored. This study aimed to analyze how secondary-level EMI science teachers incorporate students' home languages in the classroom. Using phenomenology as a research design, we collected data from two science teachers teaching at English medium public schools in Sunsari through in-depth interviews and analyzed the data thematically. The study found that secondary-level EMI science teachers frequently use Nepali and English and incorporate students' home languages purposefully, a practice known as translanguaging. Additionally, the study found that teachers use translanguaging as a pedagogical tool and a form of resistance in EMI science classrooms to enhance engagement, comprehension, and inclusivity while challenging monolingual policies. It suggests that multilingual strategies like translanguaging can foster change and reform policies through teacher agency at the micro level.